ANALISIS SERVICE QUALITY TERHADAP KEPUASAN KONSUMEN PADA TRANSPORTASI UMUM BUS EFISIENSI (PO. EFISIENSI RUTE YOGYAKARTA, PURWOKERTO, PURBALINGGA, DAN CILACAP) - Pangesti, Winda; Setyono, Hendro (Jurnal Fokus Manajemen Bisnis, 2016)
This research has a purpose to know the influence of five dimension of service quality that is, Reliability, responsivness, assurance, emphaty, and tangible may  affect statification bus route Efisiensi Yogyakarta, Purwokerto, Purbalingga dan Cilacap. Quantitative type research. Sampling with purposive sampling that has the minimum criteria  ever  ride  bus  2  times.  Data  collection  used  questionnaries  with  validity  and reliability testing, in the data analysis using multiple regression analysis, t test, f test, and R square. the subjects of this research are the pasanggers of the bus Efisiensi of Yogyakarta route, Purwokerto, Purbalingga, and Cilacap. The result of the study 1) reliability affect consumer statifications  2) responsivnes does not affect costumer statifications 3) assurance affect costumer statifications 4) emphaty affect costumer statifications and 5) tangible affect to costumer  statifications. Together, reliability, assurance, responsivness, emphaty and tangible have a  significant effect on statifications. By regression equations Y = 0,387 + 0,260X1 – 0,003 X2 + 0,251 X3 + 0,198 X4 + 0,226X5. R square of 0,639 or 63,9% is influential and the remaining 36,1% is influenced by other variabels that are not in the research.